When Does Rigorous Impact Evaluation Make a Difference? The Case of the Millennium Villages - Clemens, Michael A.; Demombynes, Gabriel (2012)
When is the rigorous impact evaluation of development projects a luxury, and when a necessity? This Paper studies one high-profile case: the Millennium Villages Project (MVP), an experimental and intensive package intervention to spark sustained local economic development in rural Africa. it illustrates the benefits of rigorous impact evaluation in this setting by showing that estimates of the project's effects depend heavily on the evaluation method. Comparing trends at the MVP intervention sites in Kenya, Ghana, and Nigeria to trends in the surrounding areas yields much more modest estimates of the project's effects than the before-versus-after comparisons published thus far by the MVP. Neither approach constitutes a rigorous impact evaluation of the MVP, which is impossible to perform due to weaknesses in the evaluation design of the project's initial phase. These weaknesses include the subjective choice of intervention sites, the subjective choice of comparison sites, the lack of baseline data on comparison sites, the small sample size, and the short time horizon. The authors describe how the next wave of the intervention could be designed to allow proper evaluation of the MVP's impact at little additional cost.